Federation Francaise d'Escrime
Homepage des Französischen Fechtverbandes This site contains a wealth of information about fencing in France, including a club list, portraits of the French National Team members, a competition calendar, tournament rules and regulations, up-to-date rankings, individual and team Olympic results, a What's New feature, and general information about fencing's history. However, French being the international language of fencing, the information is only provided in that language.